Carbon Emission and Endogenous Growth Between Two Economic Systems - Sun, Peng; Li, Shijie; Zhou, Kechong (Frontiers in Energy Research, 2021)
In recent years, many scholars have shown an increasing interest in the problem of pollution (carbon emission) in the endogenous growth but less concern about the interactions of polluting activities between two economy systems. This study explains the effects of carbon emission on the optimal balanced growth path by establishing an endogenous growth model involving exhaustible resources, human capital, physical capital, and labor time under one economy and a similar system involving two economic systems. The second system is used to analyze the interactions of polluting activities across the two economic systems that it covers. The results show that the negative externality (carbon emission) caused by one economy will bring remarkable adverse impacts on the optimal resource extraction and growth rates of other economies. If the people in one economy pay greater attention to the environmental problem (carbon emission), its own resource input will be lowered to reduce carbon emissions, but carbon emissions of another economy will be increased simultaneously to accelerate the economic growth. That is why carbon emission is one of the most challenging issues in global governance. Therefore, the global environmental pollution control needs the help of the cross-regional governance mechanism.